Your gardening year : how to make the most of every month in your garden - Horne, Alice; Pattullo, Alice (DK Publishing, 2022)
"This easy-to-use gardening guide is packed with essential tasks and top tips for every month of the year, with sections on general garden care, growing fruit and vegetables, and getting the best out of containers. Discover which plants will look their best each month and mark the progression of the seasons with a dedicated note section so you can record your garden successes and make plans for next year. With beautiful illustrations to accompany each month, Your Gardening Year is a must-have resource for all gardeners--whether you're looking for a handy at-a-glance guide for yourself or a gift for a green-fingered loved one. A must-have volume for the novice gardener looking for tips and tricks as they get into the rhythm of the gardening year, and doubling up as great gift purchase for the gardening lover in your life!" --